First observation of forward Z→bb[bar] production in pp collisions at √s=8TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; et al. (Physics letters, 2018)
The decay Z→bb¯ is reconstructed in pp collision data, corresponding to 2 fb−1 of integrated luminosity, collected by the LHCb experiment at a centre-of-mass energy of s=8 TeV. The product of the Z production cross-section and the Z→bb¯ branching fraction is measured for candidates in the fiducial region defined by two particle-level b-quark jets with pseudorapidities in the range 2.2<η<4.2, with transverse momenta pT>20 GeV and dijet invariant mass in the range 45<mjj<165 GeV. From a signal yield of 5462±763 Z→bb¯ events, where the uncertainty is statistical, a production cross-section times branching fraction of 332±46±59 pb is obtained, where the first uncertainty is statistical and the second systematic. The measured significance of the signal yield is 6.0 standard deviations. This measurement represents the first observation of the Z→bb¯ production in the forward region of pp collisions.
Available online 5 December 2017
The LHCb Collaboration: R. Aaij, P. d'Argent, S. Bachmann, D.Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewieck, S. Esen, D. Gerick, J.P Grabowski, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecná, B. Leverington, J. Marks, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und weitere]
Gesehen am 16.07.2019